Effectiveness Of Work From Home (Wfh) On Teacher Performance In Batam - Nelly Chandrawati Manalu; Mulyadi Mulyadi (IAIC Publishing, 2021)
The purpose of this study is to analyze effective work from home on leadership, competency, taining, and facility and technology to teacher performance. The design used is hypothesis testing using Statistical Package for the Social Sciences (SPSS). The population and respondents in this study was teachers in Batam city. The results of the study show that the leadership has no significant effect on teacher performance with significant = 0.360 and competency has significant effect to teacher performance with significant value = 0,036 results on training has significant effect on teacher performance with significant 0,005, and facility and technology also has significant effect on teacher performance with value of significant is 0,000. The results show that between leadership, competency, training, facility and technology together influence teacher performance with significant 0,000. Based on the two tests above between the Uji t and Uji F test and the direct test, it can be concluded that the rules of the leadership do not have a significant impact on the performance of teachers for that the schools, management and education offices focus on competency of teacher on conduct class on line or PJJ. Based on the result for adjusted R square can be explained at 51,7% is influenced by the four variables (Leadership, Competency, Training, Facility and Technology) to teacher performance, the other 48.3% is the contribution of other variables not included in this research. According to results testing in this research training, facility and technology significantly impact on teacher performance in PJJ class, which means governance and school management, provide some course training to increase teacher performance. Next research model can be explain with mediating variabel to make sure and increase adjusted R square results for example variabel the role of organizational commitment in organizational structure, organizational strategy and management.